Therapeutic Activities and Phytochemistry of Physalis Species Based on Traditional and Modern Medicine - Fatemeh Mirzaee; Amir Saeed Hosseini; Romina Askian; Mohammad Azadbakht* (Iranian Society of Pharmacognosy, 2019)
Physalis, the fifth largest genus of the Solanaceae family, consists many species which are used as food and natural remedies. Phytochemical investigations on Physalis species have led to characterization of important secondary metabolites such as withaphysalins, physalins and phytosterols which are responsible for wide range of pharmacological effects such as potent cytotoxic activity against various type of human cancer cell lines, immunomodulatory and cancer chemopreventive effects. Theyare widely used in the indigenous system of medicine for treatment of kidney and urinary disorders, leishmaniasis, inflammations, skin infections and etc. Based on Iranian traditional medicine texts, Physalis is effective for treatment of several disorders such as asthma, liver, kidney and bladder dysfunctions, wounds, hemorrhoids, and helminthic diseases. Based on recent surveys, many of the above properties have not been investigated so far except the for the healing effects on liver dysfunction. This review might be a starting point for the development of the new therapeutic applications and more investigations on Physalis species in the future.